Ameliorative Effect of Linalool in Cisplatin-Induced Nephrotoxicity: The Role of HMGB1/TLR4/NF-κB and Nrf2/HO1 Pathways - Maged E. Mohamed; Yamen S. Abduldaium; Nancy S. Younis (Biomolecules, 2020)
Background: The monoterpene linalool is a well-known essential oil component produced by several aromatic plants. Cisplatin is a widely used anticancer drug that produces many side effects, particularly nephrotoxicity. Here, we aimed to inspect linalool’s protective activity against cisplatin-induced nephrotoxicity and explore part of the underlying mechanisms. Methods: Male Wistar rats were given linalool (50 and 100 mg/kg/day orally) for 15 days; then challenged with cisplatin (8 mg/kg) on the 12th day. Renal function parameters, oxidative stress, inflammatory and apoptotic markers, and toll-like receptor pathway gene, and protein expressions were investigated. Histopathology, immunohistochemistry, and cell-line mediated cytotoxicity assays were conducted. Results: Linalool ameliorated kidney function after cisplatin challenge and managed all oxidation system parameters including GSH, SOD, CAT, MDA, NADPH, and particularly the Nrf2-mediated pathway markers. Linalool decreased TLR4, MYD88 and TRIF gene and protein expressions; diminished related inflammatory mediators such as TNF-α, IL-1β, IL-6, and NF-κB; and down-regulated HMBG1. Linalool mitigated cisplatin-induced apoptotic markers such as caspase 3, caspase 9, and Bax expression, and boosted the anti-apoptotic Bcl2 expression. Linalool potentiated the cytotoxic effect of cisplatin when investigated on HeLa and PC3 human cancer cell lines. Conclusion: Linalool could protect against cisplatin-induced kidney function and tissue damage.